2019
DOI: 10.1186/s12884-019-2391-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional service needs of pregnant and lactating adolescent girls in Trans-Mara East Sub-County, Narok County: focus on access and utilization of nutritional advice and services

Abstract: Background An understanding of the association between adolescent nutrition, adolescent pregnancy and their quest for healthcare services may elucidate a basis for intervention and formulation of programs that enhance post-partum and increase the lifespan of the newborn, improve the quality of life and bridge morbidity, mortality and healthcare-associated cost. However, the nutritional needs of pregnant and lactating adolescent girls aged below 10 years resident in Trans Mara East Sub-County, Keny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…We initially determined sample size using the Cochran formula [12], which allowed for calculation of an ideal sample size given a desired level of precision, desired confidence level, and the estimated proportion of the attribute present in the population. A total sample size of 292 was applied as previously reported in our work [13]. Proportionate distribution was done across 25 clusters equivalent to villages and by adolescent status (i.e.…”
Section: Sample Size Determination For Quantitative Approachmentioning
confidence: 99%
“…We initially determined sample size using the Cochran formula [12], which allowed for calculation of an ideal sample size given a desired level of precision, desired confidence level, and the estimated proportion of the attribute present in the population. A total sample size of 292 was applied as previously reported in our work [13]. Proportionate distribution was done across 25 clusters equivalent to villages and by adolescent status (i.e.…”
Section: Sample Size Determination For Quantitative Approachmentioning
confidence: 99%
“…Trans Mara East Sub-County was purposively selected since it is the smallest in size (275.4 km 2 ), among the four sub-counties in Narok County and had the highest prevalence of teenage pregnancies [9]. To achieve the objectives of this formative study, a cross-sectional study employing concurrent nested quantitative priority mixed methods approaches with both quantitative and qualitative research techniques was applied as previously reported in our work [10]. In this case, quantitative data were given priority while qualitative data were applied to triangulate some relevant quantitative components.…”
Section: Study Setting and Research Designmentioning
confidence: 99%
“…Sample size was determined using the Cochran formula [11], which allowed for calculation of an ideal sample size given a desired level of precision, desired confidence level, and the estimated proportion of the attribute present in the population. A total sample size of 292 was applied as previously reported in our work [10]. As previously indicated, proportionate distribution was done across 25 clusters equivalent to villages and by adolescent status (i.e.…”
Section: Sample Size Determination For Quantitative Approachmentioning
confidence: 99%
See 2 more Smart Citations